2014
DOI: 10.1021/jp5065787
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Magnetodielectric Coupling by Surface Functionalization of Nickel Nanoparticles in Ni and Polyvinylidene Fluoride Nanohybrids

Abstract: A facile surface hydroxylation treatment to modify the surface of nickel nanoparticles dispersed in ferroelectric polyvinylidene fluoride (PVDF) is reported. A remarkable increase in the amount of polar β phase of PVDF has been observed upon dispersion of nickel nanoparticles in the PVDF matrix. The leakage current reduces drastically in the composite with surface-modified nickel nanoparticles. This improvement has been observed with concurrent enhancement of electrical polarization in the surfacemodified nick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 38 publications
(77 reference statements)
2
37
1
Order By: Relevance
“…This implies that the β-phase induction effect of the BaTiO 3 nanoparticles was greatly improved by the plasma modification. This result was consistent with the reports on surface-modified nickel −PVDF composite by Mandal et al [45] and the PVDF/CNT system prepared by solution sonication by Yu et al [46]. Melting curves of the PVDF/BaTiO 3 membranes at different processing voltages are displayed in figure 6.…”
Section: Characterization Of the Functionalized Batiosupporting
confidence: 91%
“…This implies that the β-phase induction effect of the BaTiO 3 nanoparticles was greatly improved by the plasma modification. This result was consistent with the reports on surface-modified nickel −PVDF composite by Mandal et al [45] and the PVDF/CNT system prepared by solution sonication by Yu et al [46]. Melting curves of the PVDF/BaTiO 3 membranes at different processing voltages are displayed in figure 6.…”
Section: Characterization Of the Functionalized Batiosupporting
confidence: 91%
“…The interaction and different phases of the CPP‐doped PVDF films and pure PVDF were investigated by using XRD (Figure b). The diffraction peaks that correspond to the nonpolar α phase at approximately 2 θ =17.6° (1 0 0), 18.3° (0 2 0), 19.9° (0 2 1), and 26.6° [(2 0 1), (3 1 0)] are completely diminished in the diffraction patterns of chlorochalcone‐doped PVDF samples, and only one peak at approximately 20.5° [(1 1 0), (2 0 0)] is prominent, which confirms the nucleation of the electroactive β polymorphs in the PCC samples . In the XRD patterns of the PCC samples that have a high concentration of chlorochalcone, we also observe a small peak at approximately 2 θ =24.3°, which is characteristic of chlorochalcone (Figure S3 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 78%
“…In the XRD patterns of the PCC samples that have a high concentration of chlorochalcone, we also observe a small peak at approximately 2 θ =24.3°, which is characteristic of chlorochalcone (Figure S3 in the Supporting Information). The amounts of the α and β phases in the samples were measured qualitatively by the ratio of the peaks intensities at 20.5° and 18.3° ( I 20.5 / I 18.3 ; Figure c) . The maximum value of the ratio is 28.3 obtained for PCC20.…”
Section: Resultsmentioning
confidence: 99%
“…11, which shows MD at 300 K and 30 kHz, it can be observed that diamagnetic PVDF and PVDF-GO samples do not show any change in dielectric constant upon the application of the magnetic field, as expected. On the other hand, the samples loaded with magnetic Fe 3 O 4 show variation in dielectric constant upon the application of the magnetic field, with the samples PVDF-Fe 3 O 4 and PVDF-GO-Fe 3 O 4 showing a MD of ∼0.035% and 0.02%, respectively, at 300 K. It may be noted that Mandal et al 59 studied the dielectric and magneto-dielectric coupling (MD%) properties of a hydroxylated Ni-PVDF based system and have observed that the magneto-dielectric coupling value of Ni-PVDF samples was about 0.02% at room temperature. Our present sample (PVDF-GO-Fe 3 O 4 ) shows a higher MD coupling (0.04%) at room temperature compared to the Ni-PVDF sample.…”
Section: Magneto-dielectric Couplingmentioning
confidence: 93%